Knowledge, attitudes and practice of healthcare workers on the use of health information technology : a mixed method descriptive survey among healthcare workers in Princess Marina Hospital, Gaborone, Botswana - Ngcobo, Keamogetse (Stellenbosch : Stellenbosch University, 2019)
Thesis (MPhil)--Stellenbosch University, 2019.